Relações de dispersão derivativas e amplitudes elementares em interações hadrônicas e altas energias - SILVA NETO, Manoel Januário da (Universidade Estadual de Campinas, 2018)
The Glauber multiple diffraction formalism connects the hadronic elastic scattering amplitude (hadron-hadron interactions) with the elementary scattering amplitude (constituent-constituent ). In this thesis the central point is a first investigation on the applicability of the derivative dispersion relations in the determination of the real part of the elementary amplitude, from suitable parametrizations for its imaginary part. With this approach, in the context of a phenomenological model previously developed, a satisfactory description of the physical quantities that characterize the elastic hadron scattering is achived, namely, the differential cross section, the total cross section and the r parameter (the ratio of the forward real and imaginary parts of the hadronic amplitude ). It is also presented a critical discussion concerning the model previously developed and, in some detail, a review of the multiple diffraction formalism and how to deduce the derivative dispersion relations from the integral ones, in the high energy region.